Effects of Family Communication during Mealtime to the Psychosocial Well-Being - Ito, Ayaka D.; Diomampo, Adrianne Jahsiel S.; Abuyo, Madelle L. (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose in this study to explain the interaction effects of family communication during mealtimes to the relationship between the frequency of family meals and the psychosocial well-being of emerging adults. The researchers used Quantitative Designs that used qualitative interviews to support quantitative findings. The researchers used the standardized Communication Effectiveness Scale to measure how effective communication is during mealtime and the Psychological Well-Being Scale by Ryff to determine the psychosocial well-being of the respondents who are emerging adults aged 18 to 22 years old and are from Laguna and Batangas. After gathering the data, the researchers further interviewed five participants to gather data regarding family mealtimes. The data gathered were analyzed through frequency distribution, weighted mean, correlation, and moderation analysis. The results showed a significant relationship between the frequency of family mealtimes and psychosocial well-being. However, family communication during mealtime did not moderate the relationship between the predictor, frequency of family mealtime, and the outcome psychosocial well-being. The study aimed The researchers intended to specifically (1) determine the usual topic that is present during mealtimes; (2) determine the level of communication effectiveness in terms of belongingness, clarity, empathy, and non-verbal communication; (3) determine the level of psychosocial well-being of the respondents in terms of autonomy, environmental mastery, personal growth, positive relations with others, purpose in life and self-acceptance; (4) determine the relationship between frequency of family meals and psychosocial well-being; and (5) determine the interaction effects of family communication during mealtime to the relationship between the frequency of family meals and the psychosocial well-being.